Synergicity of Sharia Financial Institutions and Sharia Economic Institutions in Optimizing the Potential of Productive Zakat - Iqbal, M.; Ramadhanti, Fazar Riski; Zahra, Nadya Az; Izzah, Bilah (Formosa Journal of Science and Technology, 2024)
The country of Indonesia with a Muslim majority population has great potential in building prosperity with a policy of paying zakat. In addition, from the many zakat distribution programs that are run in Indonesia from Islamic economic institutions and other institutions, there are still many consumptive compared to productive ones. Whereas productive zakat can make mustahiq have sustainable income to meet the needs of life and overcome poverty problems. So there needs to be a solution so that zakat productive in Indonesia is more developed and advanced. Based on the above phenomenon, this study discusses Strengthening the Integration of Islamic Financial Institutions and Sharia Economic Institutions in Optimizing the Potential of Productive Zakat (Synergy Between Commercial Banks, Baznas, and Indonesian Mosque Council). Such as mapping (Mapping) carried out by mosques to find out data on muzzaki and mustahiq around mosques, coordination between Islamic banks together with BAZNAS to provide assistance and training for mustahiqs who run businesses, socialization of programs from Islamic banks that can be carried out by mosques to optimize zakat potential around the mosque, and mapping mustahiq through banking products.